Neurological Outcomes After Surgical or Conservative Management of Spontaneous Spinal Epidural Abscesses: A Systematic Review and Meta-Analysis of Data From 1980 Through 2016. Issue 1 (February 2019) - Wang, Timothy Y.; Harward, Stephen C.; Tsvankin, Vadim; Bell, Hannah; Charalambous, Lefko; Adil, Syed M.; Englot, Dario J.; Goodwin, C. Rory; Karikari, Isaac O.; Isaacs, Robert E.; Krucoff, Max O.
Abstract : Study Design: This is a meta-analysis. Objective: Perform a systematic review and quantitative meta-analysis of neurological outcomes from all available spinal epidural abscess (SEA) literature published between 1980 and 2016. Summary of Background Data: Current literature on SEAs lacks large-scale data characterizing prognostic factors and surgical indications. Materials and Methods: PubMed was queried for studies reporting neurological outcomes from patients undergoing conservative or surgical management for spontaneous SEA. Inclusion criteria included outcomes data measured ≥6 months after presentation, ≥10 human subjects, and diagnosis by magnetic resonance imaging or Computed tomography-myelogram. Where available, demographic data, abscess location, comorbidities, pretreatment neurological deficits, treatment methods, bacterial speciation, and complications were extracted from each study. Potential outcome predictors represented by continuous variables were compared using student t test and categorical variables were compared using the Pearson χ 2 test. Variables identified as potentially associated with outcome ( P ⩽0.05) were subjected to meta-analysis using Cochran-Mantel-Haenszel testing to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results: In total, 808 patients were analyzed from 20 studies that met inclusion criteria. 456 (56.3%) patients were treated with surgery and antibiotics, and 353 (43.7%) patients were managed with antibiotics alone. Neither surgical intervention (OR=1.01, 95% CI=0.40–2.59), lumbosacral location (OR=1.51, 95% CI=0.23–9.79), nor neurological deficit on presentation (OR=0.88, 95% CI=0.40–1.92) were significantly associated with good (stable or improved) or bad (worsened) neurological outcome, whereas delayed surgery was significantly associated with bad outcome (OR=0.01, 95% CI=0.02–0.62) and cervicothoracic location approached significance for predicting bad outcome (OR=0.41, 95% CI=0.15–1.09). Conclusions: Current literature does not definitively support or oppose surgical intervention in all SEA cases. Therefore, until better evidence exists, the decision to operate must be made on an individual case-by-case basis with the goals of preventing neurological decline, obtaining source control after failed conservative treatment, or restoring spinal stability.